The Correlation between E-Book Utilization and Students' Self-Directed Learning at MAN 2 Pekanbaru - Dian Eka Tivenda; Rini Asmara (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The implementation of digital learning requires effective learning resources that can support students’ autonomy and engagement in the learning process. However, empirical evidence regarding the relationship between e-book utilization and self-directed learning among secondary school students remains limited. This study examined the relationship between e-book utilization and students’ self-directed learning at MAN 2 Kota Pekanbaru. A quantitative approach with a correlational survey design was employed, involving 88 students selected through proportional random sampling. Data were collected using questionnaires and analyzed through descriptive statistics, Pearson correlation, and the coefficient of determination. The findings showed that both e-book utilization and students’ self-directed learning were categorized as good. A strong positive relationship was identified between e-book utilization and self-directed learning (r = 0.769), with e-book utilization accounting for 59.1% of the variance in students’ self-directed learning. These findings indicate that greater utilization of e-books is associated with higher levels of student autonomy in learning. The study concludes that optimizing e-book use can support the development of self-directed learning and strengthen the implementation of digital learning in schools. This study provides practical implications for schools and educators in designing digital learning strategies that promote students’ independence, responsibility, and active engagement in learning.